2018
DOI: 10.1016/j.ydbio.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

WAVE regulates Cadherin junction assembly and turnover during epithelial polarization

Abstract: Actin is an integral component of epithelial apical junctions, yet the interactions of branched actin regulators with apical junction components are still not clear. Biochemical data have shown that α-catenin inhibits Arp2/3-dependent branched actin. These results suggested that branched actin is only needed at earliest stages of apical junction development. We use live imaging in developing C. elegans embryos to test models for how WAVE-induced branched actin collaborates with other apical junction proteins d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 62 publications
(95 reference statements)
4
21
0
Order By: Relevance
“…In Pten −/− EBs, increased amounts of Abi1 and excessive WRC activation may lock actin in the cell cortex and thus prevent epiblast differentiation and polarization. Furthermore, in the Caenorhabditis elegans intestinal epithelium, similar relocation of the WRC is suggested to facilitate the lateral movement of E-cadherin to the apical side and promote the assembly of apical adherens junctions (Sasidharan et al, 2018). Taken together, our data support the following hypothesis: during epiblast morphogenesis, PTEN dephosphorylates Abi1 and down-regulates the WRC at the cell cortex.…”
Section: Discussionsupporting
confidence: 79%
“…In Pten −/− EBs, increased amounts of Abi1 and excessive WRC activation may lock actin in the cell cortex and thus prevent epiblast differentiation and polarization. Furthermore, in the Caenorhabditis elegans intestinal epithelium, similar relocation of the WRC is suggested to facilitate the lateral movement of E-cadherin to the apical side and promote the assembly of apical adherens junctions (Sasidharan et al, 2018). Taken together, our data support the following hypothesis: during epiblast morphogenesis, PTEN dephosphorylates Abi1 and down-regulates the WRC at the cell cortex.…”
Section: Discussionsupporting
confidence: 79%
“…Previous work has demonstrated an important role for ABI1 (Ryu et al, 2009; Xiong et al, 2012) and the Wave complex (Lee et al, 2016; Sasidharan et al, 2018) in AJ homeostasis. The pattern of β-catenin immunostaining in Abi1 KD IFE had suggested that AJ formation was unaffected by the loss of Wave complex function (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…To rule out the possibility that the lack of neuroectoderm involution is due to a lack of pharynx retraction, where HMR-1 is known to localize to its apical side ( Sasidharan et al, 2018 ), we measured the posterior movement of the anterior tip of the pharynx. Retraction is not significantly altered in any of the 12 hmr-1 mutant embryos assessed ( Figure 2c ), with an average of 17 microns involution in hmr-1 mutants vs 18 microns for WT.…”
Section: Resultsmentioning
confidence: 99%